Purine Synthesis De Novo in Lymphocytes from Patients with Gout - Gordon, R. B.; Counsilman, A. C.; Cross, S. M. C.; Emmerson, B. T. (Clinical science (1979), 1982)
1. Variables that affect the measurement of purine synthesis de novo in human lymphocytes were studied and a reliable method of measurement of purine synthetic activity in these cells was established. 2. Purine synthesis de novo was measured as the rate of incorporation of [14C]formate into α-N-formylglycinamide ribonucleotide when further steps in the biosynthetic pathway had been blocked by azaserine. Incubation was carried out in a synthetic medium with a high phosphate concentration (25 mmol/l). 3. Purine synthesis de novo was measured in lymphocytes obtained on several occasions both from control subjects and from patients with gout, particularly those who tended to overproduce urate as suggested by high values of urinary urate. 4. Lymphocytes obtained from each individual on different occasions showed considerable variations in purine biosynthetic activity. This variation was such that there was no difference between the mean values obtained for the gouty subjects and the control subjects. 5. No correlation was obtained between the mean purine synthetic activity de novo in lymphocytes and either the serum urate concentration or the 24 h urinary urate excretion on a purine-free diet. 6. Apart from those with recognized enzyme mutations, no subgroup of the gouty population has been demonstrated in whom isolated lymphocytes demonstrate an intrinsic abnormality of purine synthesis de novo.